Board Diversity, Competitive Advantage, Firm Size and Firm Value: A Case on Indonesian Materials Industry - Saputra, Arjun; Nuzula, Nila Firdausi (FIA UB, 2024)
This study aims to analyze and explain the effect of board diversity, competitive advantage, and firm size on firm value in basic materials sector companies listed on the Indonesian Stock Exchange from 2017 to 2022. The sample of this study used 30 companies from a population of 42 companies that met the sampling criteria, and this study used Partial Least Squares (PLS) method. The results show that board diversity has a negative and significant effect on firm value, competitive advantage has a positive and significant effect on firm value, and firm size has a positive and significant effect on firm value. Board diversity has a significant negative effect on firm value, highlighting the importance of consideration in the formation of an inclusive and diverse board composition. On the other hand, the finding that competitive advantage and firm size have a significant positive effect on firm value suggests that internal factors such as economies of scale, capital requirements, and firm size play an important role in determining firm value. These findings provide valuable insights for business practitioners to enhance firm value in the Indonesian natural resources industry.